Essential MATLAB for engineers and scientists - Hahn, Brian D. 1946-2005; Valentine, Daniel T. 1946- (Academic Press, 2013)
This book provides a concise, balanced overview of the functionality in MATLAB. It facilitates independent learning with coverage of both the fundamentals and applications in two parts. The essentials of MATLAB are illustrated throughout with many examples from a wide range of familiar scientific and engineering areas, as well as from everyday life. This is an ideal textbook for a first course on MATLAB or an engineering problem solving course using MATLAB, as well as a self-learning tutorial for professionals and students who are expected to learn and apply MATLAB themselves